Pengaruh Pupuk Urea dan Interval Panen Terhadap Pertumbuhan dan Produksi Kangkung Air (Ipomoea aquatica Forsk.) - Yoseph Marthin Sibarani; JA Napitupulu; Ratna Rosanty Lahay (Universitas Sumatera Utara, 2015)
The demand for water spinach is increasing but this commodity is not cultivated intensively. Theexperiment aims was to know the optimal interaction of harvest interval and application urea toincrease and maintain production of water spinach. Research was conducted to determine theoptimal effect of application urea and harvest interval to the regrowth and production of waterspinach at Tanjung Raya street, Medan Helvetia on January-June 2014 using split plot design withtwo factors, the factors were dose of urea (0;25;50;75g/plot/season) and harvest interval (every 8,10, 12 days after the first harvest). The parameters observed were shoots numbers, shoots length,primary and secondary branches number, fresh weight, consumable fresh weight per sample andproduction per plot. The results showed that the application urea with 75g/plot/season is better than0, 25 and 50 g/plot/season at the same time harvest interval treatment with 8 days is better than 10and 12 days after the first harvest.Key words : water spinach, urea, harvest interval.